Volatile constituents and trace metal analysis of Alpinia conchigera griff. / Haslinda Mohd Salleh - Mohd Salleh, Haslinda (2014)
The rhizomes and leaves of Alpinia conchigera were extracted by supercritical fluid extraction (SFE) technique using liquid carbon dioxide at constant temperature (40°C) with two different pressures (A1: leaves extract at 1500 psi; A2: leaves extract at 5000 psi; B1: rhizomes extract at 1500 psi; B2: rhizomes extract at 5000 psi). The volatile constituents of the extracts were detected by GCMS. The major compound was identified as acetoxychavicol acetate in all the extracts. Besides that, β- bisabolene, chavicol, trans-pcoumaryl diacetate and acetoxyeugenol acetate were detected too. The concentration of macronutrients and trace metal for rhizomes and leaves of Alpinia conchigera were determined using microwave digestion method and analyzed by Flame Atomic Absorption Spectroscopy (FAAS). From the analysis on rhizomes and leaves of Alpinia conchigera, the dominant metals are Ca and Mg respectively while the Cu content is the least in all samples. B2 showed strong inhibition against dermathophytic fungi (Trichophyton mentagrophytes) whereas A1 and A2 revealed moderate inhibition against Microsporum canis, Trichophyton mentagrophytes and Trichophyton rubrum. Therefore, the rhizome extracts of Alpinia conchigera (B2) is more effective compared to the leaves extracts of Alpinia conchigera (A1 and A2).